Placenta accreta: the silent invader - Dwivedi, Seema; Dwivedi, Gopaal Narayan; Kumar, Archana; Gupta, Neena; Malhotra, Vinita; Singh, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To review incidence causes, clinical presentations, management, maternal mortality and morbidity associated with placenta accreta. Methods: A prospective study was carried out at the Department of Obstetrics and Gynaecology, GSVM Medical College, Kanpur during the period of January 2010 to December 2014. During this period all the patients who were diagnosed with placenta accreta were included in the study. Results: Majority of patients presenting with placenta accreta belonged to age group 30-35 years (46%) were multigravida (95%) came from both rural and urban background. Majority of deliveries complicated by placenta accrete were booked cases (78%). Previous LSCS with placenta previa proved to be the major cause (86%). Out of whole spectrum including placenta accreta, increta, percreta, placenta accreta was the commonest of all and placenta percreta required maximum number of blood transfusions (5-6 units of blood on an average). Hysterectomy was required in 29 cases out of 37 (78%), 6 women suffered from bladder injury which were repaired. Among total of 37 women 7women couldn’t be saved even after our best of efforts. Conclusions: Incidence of placenta accrete has increased now a days because of increased incidence of cesarian sections, placenta accreta was seen in primi due to uterine procedures done deliberately in both diagnostic and therapeutic indications. Morbidly adherent placenta is always a nightmare for the obstetrician. Suspicion of a case on history, preoperative confirmation of diagnosis, planned management with bundle of care, with multi-disciplinary approach can save many patients from the clutches of inevitable death.